Sobre el transporte de partículas en cuerpos oceánicos semicerrados (ING) - Quirós Álvarez, Guillermo (1984)
It is known that residual flow, established as a consequence of the interaction between the wave and the bottom profile, plays a relevant roll in the transport of particles in suspension, larvae and some pollutants, mainly. The most meaningful analysis have been carried out, successfully, employing non linear numerical models, the most of them barotropic.